Establishment and optimization of a tobacco rattle virus -based virus-induced gene Silencing in Atriplex canescens - Shan Feng; Jin-Da Chen; Ai-Ke Bao (Plant Methods)
Abstract Atriplex canescens, a halophytic model plant exhibiting remarkable tolerance to abiotic stress, possesses valuable genetic resources for crop improvement. However, the absence of a reliable and stable transformation systems has impeded the functional characterization of candidate genes in this species. In this study, we established an efficient virus-induced gene silencing (VIGS) system in A. canescens by constructing a tobacco rattle virus (TRV)-based vector targeting the phytoene desaturase gene (AcPDS), whose silencing induces an easily recognizable photobleaching phenotype. Through comparative analyses of inoculation materials and methods for VIGS implementation in A. canescens, we found that inoculating germinated seeds with Agrobacterium suspension (OD600 = 0.8) carrying TRV2:AcPDS vectors through vacuum-assisted agroinfiltration (0.5 kPa, 10 min) further achieving an average silencing efficiency of approximately 16.4%. Systemic photobleaching phenotypes appeared in newly emerged leaves at about 15 days post-inoculation, accompanied by a 40–80% reduction in AcPDS transcript abundance, as confirmed by qRT-PCR. Furthermore, we successfully validated this VIGS system by silencing two aquaporin genes (AcTIP2;1 and AcPIP2;5), achieving 60.3–69.5% knockdown efficiency, which confirmed the broad applicability of this system in A. canescens. In summary, our method provides a reliable reverse-genetics platform that facilitates the study of stress-resistance mechanisms in A. canescens, effectively overcoming previous technical limitations in genetic research on this species.